THE USE OF THE MOVIE “THE GOOD DOCTOR” AS TEACHING MEDIA IN ESP - Silva Aulia (Journal of English Education Program (JEEP), 2022)
This study aims to determine the vocabulary needed by medical students and students' perceptions of the film "The Good Doctor" as a teaching media for English vocabulary for medical students. This research which uses a qualitative case study design is conducted in a Vocational School in Tasikmalaya. To collect data, the researcher combines the data obtained from thirty-one participants consisting of one English teacher and thirty medical students using semi-structured interviews and an open questionnaire. The results of semi-structured interviews shows that the English vocabulary needed by medical students contains a collection of English vocabulary-specific terms for drugs, diseases, medical equipment, etc. Meanwhile, the results of the open-ended questionnaire based on students' perceptions indicate that medical vocabulary is important because learning English vocabulary can increase students' knowledge. Mainly, special vocabulary and learning English medical vocabulary is useful for their careers. Finally, the researcher provides suggestions on how to increase the needs of vocational students, especially the English vocabulary needed by medical students. The education of this research is to allow the teachers to use films for teaching media in ESP classes.